Perubahan Komposisi Kimia, Aktivitas Antioksidan, Vitamin C dan Mineral Tanaman Genjer (Limnocharis flava) Akibat Pengukusan - Nurjanah Nurjanah; Agoes M Jacoeb; Roni Nugraha; Marisa Permatasari; Tri Kalbu Ardiningrum Sejati (UII, 2014)
Yellow velvetleaf (L. flava) is a type of aquatic plants commonly consumed by the public. Yellow velvetleaf steamed of processing products. The purpose of research was to determine the effect of steaming period on chemical composition, antioxidant activity, ascorbid acid, and minerals on yellow velvetleaf. Chemical composition of fresh yellow velvetleaf consisted of 93.92% of water, 0.20% of fat, 2.38% of protein, 0.70% of ash, 0.10% of acid soluble ash, 2.70% of carbohydrate and 1.31% crude fiber. Steaming caused a decrease in water levels and increased levels of fat, protein, ash, carbohydrate and crude fiber yellow velvetleaf. Phytochemical components of the three crude extracts yellow velvetleaf (fresh, steamed 3 and 5 min) were steroids, saponins, phenol hydroquinone and reducing sugar. Antioxidant activity of the crude extracts was 131 ppm and steaming for 3 minutes and 5 minutes increased IC50 value to 1350 ppm and 3409 ppm, respectively. In conclusion steaming proses changed the antioxidant activity of yellow velvetleaf. Losses of ascorbid acid of fresh genjer were 3.20% and 11.15% correspondingly after 3 and 5 minutes steaming. Beta carotene in fresh genjer decreased by 20.02% (steamed 3 minutes) and 60.90% (steamed 5 minutes). Minerals respectively were decreased due to steaming. Hightest mineral loss happened to natrium with 70.44% (steamed 3 minutes) and 82.87% (steamed 5 minutes). Total minerals loss in steaming for 3 minutes was 26.60% and the for 5 minutes was 45.40%. Keyword: antioxidant activity, ascorbid acid , beta caroten , bioactive components, mineral, proximate, yellow velvetleaf (Limnocharis flava).